Study of Numerical Indications of Elixir Derived from Medicinal Plants - Abdijalilova Zilola Khikmatullaevna; Ergasheva Dilafruz Zaripovna; Zaynutdinov Khikmatulla Sunnatovich (Scientific Trends, 2025)
Upper respiratory tract diseases are one of the most common diseases worldwide. Children are particularly susceptible to respiratory tract diseases: 54.2% of all diseases in them are respiratory system diseases. This figure is 33.2% in adolescents and 13.6% in adults. In the treatment of inflammatory diseases of the upper respiratory tract, based on the symptoms of the disease, it is recommended to reduce the swelling of the mucous membrane, use sprays and aerosols in the early stages of the disease, use antibiotics in the late stages of the disease, systemic treatment with antibiotics, as well as the use of mucolytics and combination drugs. The elixir dosage form we offer uses local raw materials, and the article is devoted to the treatment of upper respiratory tract infections. The quality of the elixir used in inflammation of the airways is determined by numerical indicators. As a result of the research, a positive result was obtained.
Keywords: Rhinitis. sinusitis, adenoiditis, goymoritis. frontitis, laryngitis, pharyngitis, bronchitis, pneumonia, bronchial asthma, liquid extract, authenticity, alcohol strength, boiling point, potentiometric.